Measurement of Adhesion of In Situ Electrospun Nanofibers on Different Substrates by a Direct Pulling Method. (27th March 2020) - Zhang, Bin; Yan, Xu; Xu, Yuan; Zhao, Huai-Song; Yu, Miao; Long, Yun-Ze
Abstract : In some cases, we hope to remove the electrospun nanofibrous mesh from the collector easily. But in some cases such as wound dressing, we observe that the in situ electrospun nanofibers can stick to the collector (e.g., skin). Therefore, the adhesion between the in situ electrospun web and the substrate becomes important in the performance and practical application of the electrospun material. In this paper, we reported a direct pulling method to measure the adhesion and understand the adhesion mechanism. In this method, we used gravity to pull the fiber directly from the substrate and then measured the gravity to calculate the adhesion. This new test method is more convenient and practical than the previously reported methods. In addition, the adhesion of the in situ electrospun web on different substrates (e.g., aluminium foil, wood pulp paper, and silicon paper) was also studied by this method. The adhesion was influenced by spinning voltage, electrical conductivity, and surface roughness of the substrates.